PEMIKIRAN MUHAMMAD NAQUIB AL-ATTAS DALAM PENDIDIKAN AKHLAK PESERTA DIDIK - Jamaludin Jamaludin (Smart Education, 2023)
Abstract: This study describes the concept of Ta'dib Muhammad Naquib Al-Attas in Character Development of Students. This research is a qualitative research that uses a pedagogical approach. The results show that the concept of Ta'dib according to Muhammad Naquib Al-Attas, the concept of Ta'dib emphasizes the mastery of correct knowledge in a person in order to produce stable charity and good behavior based on faith. The concept of Ta'dib, first, as a moral competence (morals) that must be possessed by educators and students, second, the formation of personality so that the psychological characteristics of a person related to the tendency to relate socially with others, especially those related to; friendliness, self-control, implementation can be said to be successful because of the adab education that is applied in the lives of students, but it must also be admitted that during the epidemic, Ta'dib education experienced a few obstacles, such as education level, environment, culture, socio-economic level and online learning.Keywords: Ta'dib; Character; Covid-19 Abstrak: Penelitian ini mengambarkan pemikiran Tadib Muhammad Naquib Al-Attas dalam Pengembangan Karakter Peserta Didik. Penelitian ini adalah penelitian kualitatif yang menggunakan pendekatan pedagogis. Konsep Tadib, pertama, sebagai kompetensi moral (akhlak) yang harus dimiliki oleh pendidik maupun peserta didik, kedua, pembentukan kepribadian agar karakteristik psikologis seseorang yang berkaitan dengan kecendrungan untuk berhubungan sosial dengan orang lain, khususnya yang berkaitan dengan; keramahan, pengendalian diri, implementasi bisa dikatakan berhasil karena pendidikan adab yang diterapkan dalam kehidupan peserta didik, namun harus diakui juga dimasa pademik pendidikan Tadib mengalami sedikit kendala, seperti tingkat pendidikan, Lingkungan, Budaya, Tingkat sosial ekonomi dan pembelajaran Daring. Hasil penelitian menunjukkan bahwa konsep Tadib menurut Muhammad Naquib Al-Attas, konsepTadib titik tekan pada penguasaan ilmu yang benar dalam diri seseorang agar menghasilkan kemantapan amal dan tingkah laku yang baik yang berlandaskan keimanan.Kata kunci: Tadib; Karakter; Covid-19